Fournier Gangrene in Newly Diagnosed Diabetes Mellitus Patient: A Case Report - Annisa Nidya Rahmatika Sitepu; Santi Syafril (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2020)
ABSTRACT: Background: Fournier gangrene (FG) is a rare but life-threatening necrotizing fasciitis of the external genitalia, perineal area, or perianal caused by a combination of aerobic and anaerobic bacterial infection. It has a higher incidence in men with risk factors including diabetes, HIV, alcoholism, and other immunocompromised states Case presentation: A man, aged 62, was admitted to the hospital complaining of ulcers on his testicles. The patient feels that his testicles are getting swollen, painful, and red. Ulcers appear black, accompanied by pus and accompanied by a foul smell. The patient was hematoligic examination, radiologic and blood cultur and diagnosed with Fournier's gangrene on scrotal area and T2DM. The patient is subjected to immediate debridement and is given broad-spectrum antibiotic therapy, administration of insulin, and monitoring of blood sugar. Conclusion: We reported a case of Fournier gangrene being comprehensive management, causing the prognosis to good improvement Keyword: Fournier gangrene, T2DM ABSTRAK: Latar belakang: Fournier Gangrene (FG) merupakan suatu fasciitis nekrotikans langka namun mengancam nyawa pada genitalia eksterna, daerah perineal, atau perianal yang disebabkan oleh gabungan infeksi bakteri aerob dan anaerobik. Penyakit ini memiliki insiden yang lebih tinggi pada laki-laki dengan faktor risiko termasuk diabetes, HIV, alkoholisme, dan keadaan imunokompromise lainnya. Presentasi Kasus: Seorang pria, berusia 62 tahun, dirujuk ke rumah sakit dengan keluhan luka borok pada buah zakarnya. Pasien merasakan buah zakarnya semakin membengkak, nyeri dan memerah. Luka borok tampak menghitam, disertai nanah dan disertai bau busuk. Pasien dilakukan pemeriksaan darah dan radiologi di diagnosis dengan Fournier gangrene scrotal area dan DMT2. Selanjunya pasien dilakukan debridemen segera, dan diberikan terapi antibiotik spektrum luas, pemberian insulin, dan dilakukan pemantauan gula darah Kesimpulan: Dilaporkan seorang kasus Fournier gangrene yang ditangani secara komprehensif, menyebabkan perbaikan prognosa. Kata Kunci: Fournier gangrene; DMT2